Silica‐Supported Au–Ag Catalysts for the Selective Hydrogenation of Butadiene. Issue 12 (12th June 2017) - Masoud, Nazila; Delannoy, Laurent; Calers, Christophe; Gallet, Jean‐Jacques; Bournel, Fabrice; de Jong, Krijn P.; Louis, Catherine; de Jongh, Petra E.
Abstract: Gold and silver are miscible over the entire composition range, and form an attractive combination for fundamental studies on bimetallic catalysts. Au–Ag catalysts have shown synergistic effects for different oxidation and liquid‐phase hydrogenation reactions, but have rarely been studied for gas‐phase hydrogenation. In this study 3 nm particles of Au, Ag and Au–Ag supported on silica (SBA‐15) were investigated as catalysts for selective hydrogenation of butadiene in an excess of propene. The Au catalyst was over an order of magnitude more active than the Ag catalyst at 120 °C. The initial activity of the Au–Ag catalysts scaled linearly with the Au‐content, suggesting a direct correlation between the surface and overall compositions of the nanoparticles and the absence of synergistic effects. All Au‐containing catalysts were highly selective to butenes (>99.9 %). The Au catalysts were stable, whereas the Au–Ag catalysts lost about half of their activity during 20 h run time at 200 °C, but the initial activity was restored by a consecutive oxidation‐reduction treatment. Near ambient pressure x‐ray photoelectron spectroscopy showed that exposure to H2 at elevated temperatures led to a gradual enrichment of the surface of the Au–Ag nanoparticles by Ag. These observations highlight the importance of considering progressive atomic rearrangements in bimetallic nanocatalysts under reaction conditions. Abstract : Better than Gold? The activity, selectivity and stability of Au, Ag and Au–Ag catalysts in gas‐phase hydrogenation and possible synergistic effects for the Au–Ag are investigated. Near ambient pressure x ‐ray photoelectron spectroscopy is used to detect atomic rearrangements and its correlation to the stability of bimetallic Au–Ag nano–catalysts under hydrogenation reaction condition.